1995
DOI: 10.1016/0014-5793(95)00758-2
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a cDNA encoding a cellobiose dehydrogenase from the white rot fungus Phanerochaete chrysosporium

Abstract: The eDNA of cellobiose dehydrogenase (CDH) fromPhanerochaete chrysosporium has been cloned and sequenced.The 5' end was obtained by PCR amplification. The cDNA contains 2310 translated bases excluding the poly(A) tail. The deduced mature protein contains 770 amino acid residues and is preceded by a 18 residue long signal peptide. The regions of the amino acid sequence corresponding to the heme and FAD domains of CDH were identified as well as the nucleotide-binding motif, the disulfide pairing and a methionine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 32 publications
3
57
1
Order By: Relevance
“…The prosequence occupies the amino acid channel acting like a plug that prevents substrate binding and perturbs active site geometry. To our knowledge, this is a novel type of proenzyme activation not yet found in proteases (10 -12), flavoproteins (13)(14)(15)(16)(17)(18), and the three-dimensional structures of other zymogens studied so far.…”
Section: Structure Of Paopt-ab Complex and Amino Acid Channel-mentioning
confidence: 83%
See 1 more Smart Citation
“…The prosequence occupies the amino acid channel acting like a plug that prevents substrate binding and perturbs active site geometry. To our knowledge, this is a novel type of proenzyme activation not yet found in proteases (10 -12), flavoproteins (13)(14)(15)(16)(17)(18), and the three-dimensional structures of other zymogens studied so far.…”
Section: Structure Of Paopt-ab Complex and Amino Acid Channel-mentioning
confidence: 83%
“…X-ray crystallographic studies of zymogens and comparisons with their counterparts have identified the structural changes that accompany this conversion. As for flavoproteins, several enzymes are expressed as proforms, such as succinate dehydrogenase from Saccharomyces cerevisiae (13), pea ferredoxin-NADP reductase (14), glucose-fructose oxidoreductase from Zymomonas mobilis (15), and cellobiose dehydrogenase from Phanerochaete chrysosporium (16). The size of the prosequence of these enzymes are 18 residues long to 5-kDa molecular mass.…”
mentioning
confidence: 99%
“…The deduced amino acid sequence of the GADH dehydrogenase subunit contained three possible glycine boxes, GFGWAG (nt 1036 to 1053), GTGTGG (nt 1282 to 1299), and GAGGAG (nt 2104 to 2121). A homology search of protein databases revealed that the region containing the first glycine box showed sequence similarity with the FAD-binding motif of cellobiose dehydrogenase (CEDH) from Phanerochaete chrysosporium (12,24), sorbose dehydrogenase (SDH) from Gluconobacter oxydans (25), choline dehydrogenase (CDH) of Rhizobium meliloti, glucose dehydrogenase of Drosophila melanogaster (38), human monoamine oxidase B (6), and versicolorin B synthase (VBS) from Aspergillus parasiticus (29). The amino acid sequence alignment is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The LS 3 band was obscured by a band at 1515 cm Ϫ1 assigned as 38 (36). When the temperature was lowered to 90 K, both enzymes exhibited similar RR spectra, with 2 , 3 , and 10 at 1577, 1507, and 1642 cm Ϫ1 , respectively, characteristic of a 6cLS heme. The electronic absorption spectra of the reduced CDH proteins (Fig.…”
Section: Engineering Novel Heme Ligation In Cellobiose Dehydrogenasementioning
confidence: 95%
“…The CDH gene from the white rot fungus Phanerochaete chrysosporium has been cloned and sequenced (2,3), revealing a full-length protein of 755 amino acids partitioned into a cytochrome domain (residues ) and a flavodehydrogenase domain (residues 216 -755) connected by a 25-residue peptide linker. A flavin adenine dinucleotide cofactor is bound to the flavoprotein domain, whereas the cytochrome domain contains a 6-coordinate low spin (6cLS) Fe-protoporphyrin IX (4,5).…”
mentioning
confidence: 99%